Effects of Expression of Streptococcus pneumoniae PspC on the Ability of Streptococcus mitis to Evade Complement-Mediated Immunity - Marshall, Helina; José, Ricardo J.; Kilian, Mogens; Petersen, Fernanda C.; Brown, Jeremy S. (Frontiers in Microbiology, 2021)
Streptococcus pneumoniae and Streptococcus mitis are genetically closely related and both frequently colonise the naso-oropharynx, yet S . pneumoniae is a common cause of invasive infections whereas S. mitis is only weakly pathogenic. We hypothesise that sensitivity to innate immunity may underlie these differences in virulence phenotype. We compared the sensitivity of S. pneumoniae and S. mitis strains to complement-mediated immunity, demonstrating S. mitis strains were susceptible to complement-mediated opsonophagocytosis. S. pneumoniae resistance to complement is partially dependent on binding of the complement regulator Factor H by the surface protein PspC. However, S. mitis was unable to bind factor H. The S. pneumoniae TIGR4 strain pspC was expressed the S. mitis SK142 strain to create a S. mitis pspC+ strain. Immunoblots demonstrated the S. mitis pspC+ strain expressed PspC, and flow cytometry confirmed this resulted in Factor H binding to S. mitis, reduced susceptibility to complement and improved survival in whole human blood compared to the wild-type S. mitis strain. However, in mouse models the S. mitis pspC+ strain remained unable to establish persistent infection. Unlike S. pneumoniae strains, culture in serum or blood did not support increased CFU of the S. mitis strains. These results suggest S. mitis is highly sensitivity to opsonisation with complement partially due to an inability to bind Factor H, but even when complement sensitivity was reduced by expression of pspC poor growth in physiological fluid limited the virulence of S. mitis in mice.